Bureaucratic overburdening in advanced democracies. - Fernández‐i‐Marín, Xavier; Hinterleitner, Markus; Knill, Christoph; Steinebach, Yves (Public Administration Review, 2024)
Constant policy growth can overburden bureaucracies if implementation capacities are not expanded in lockstep with policy production. This development may undermine policy effectiveness and hence the long‐term legitimacy of democracies. This article provides a systematic analysis of this phenomenon. We demonstrate that (i) overburdening is a general trend in advanced democracies; (ii) the extent of overburdening varies by the institutional context in which policy makers operate; and that, in consequence, (iii) countries' bureaucracies differ in their distance (or closeness) to the "tipping point" after which additional policies do more harm than good. We provide information on the ratio between the policies up for implementation and the bureaucratic capacities available for 21 OECD countries over a period of 45 years (1976–2020), focusing on the areas of environmental and social policy as two major areas of governmental intervention. Bayesian analyses and background interviews serve to illuminate the reasons for and consequences of overburdened bureaucracies.